Effect of ciling up to the failure of concrete determined by acoustic emission - J. HOŁA (Archives of Acoustics)
Results showing how the oiling up of concrete series, differing in their aggregate grading, affects their failure are presented. The acoustic emission was used in the test. The determined values of initiating stress, σi, and critical one σcr, in the oiled up concrete and the reference, unoiled up concrete prove that oiling up affects significantly the failure of the concrete. It has been found that the oiling up of concrete results in the reduction of the values of the initiating and critical stress compared to the values of these stresses in the reference unoiled concrete series. The tests have shown this reduction to be practically independent of the concrete's aggregate grading.